SEMG-based research of upper body muscle fatigue during manual material handling. (2018) - Yu, Na; Zhang, Chang
The upper body muscles frequently contract during manual material handling tasks, and muscle fatigue could arise during the repetitive contraction. To explore the muscle fatigue within arm, shoulder and back during material handling, 11 male graduate students were chosen as subjects to simulate furniture boards handling task. In the experiment, the vertical lifting distance, set three levels, was the single test variable. Through analysing normalised average electromyography (Normalised AEMG) and mean power frequency (MPF) of the electromyography signal collected during the experiment, found that the biceps brachii muscle the most relaxed, and the multifidus muscle the most fatigable. In order to reduce waist muscle load, it is suggest that operators increase their use of arm strength during material handling, optimising work posture.